Juridical review of the judge's decision exceeding the demands of the prosecutor in the case of the crime of premeditated murder of a police officer - Fauziah Nuryulianti; Sugeng Djatmiko; Nia Sari (Institute Of computer Science (IOCS), 2023)
The state must be present to provide justice for every citizen who has been deprived of his life. This study aims to review juridically how the Judge's decision Number 797/Pid.B/2022/PN.Jkt. The cell is related to the criminal act of premeditated murder against a member of the police where the sentence exceeds the prosecutor's demands. The type of research used in this research is normative legal research, with the Criminal Code as the primary legal material. The approach used is the statutory approach, the conceptual approach and the case approach. This study concludes that the crime of premeditated murder is regulated in Article 340 of the Criminal Code which carries a death penalty or life imprisonment or a maximum of 20 (twenty) years. In connection with the judge's considerations in the case study, it was explained that there were several things that were aggravating to the defendant PC as a co-perpetrator who actually became a key witness in this case. The defendant also convoluted and was not honest in giving testimony at trial, which made it difficult for the trial and instead positioned himself as a victim of abuse